Transformation of Early Childhood Education: Integrating Technology in Early Childhood Learning - Pascalian Hadi Pradana; I Made Sutajaya; I Wayan Suja (Pt. Anagata Sembagi Education, 2024)
This study aims to identify, analyze, and summarize the findings of various previous studies on the use of technology in early childhood education (ECE) through the Systematic Literature Review (SLR) method. This method was chosen because it provides a comprehensive understanding by reviewing various relevant articles, journals, and research reports. The SLR process begins with the identification of inclusion and exclusion criteria, which are used to select the studies analyzed. Data were collected from various sources such as academic journals, conference articles, and research reports in the last five years. The main focus of this study is to evaluate the effectiveness of technology in supporting early childhood learning, as well as the challenges and opportunities faced by educators in integrating technology into the ECE curriculum. The results of the study indicate that technology has great potential to transform ECE education, increasing children's engagement, creativity, and learning abilities. However, the success of technology integration is highly dependent on the readiness of educators to utilize technology effectively and adequate access to technological devices. Therefore, educator training and the provision of appropriate infrastructure are essential to maximize the benefits of technology. Further research is needed to explore the best strategies for integrating technology into the ECE curriculum and to identify policies that can support the widespread implementation of technology in the ECE sector.